Irrigation scheduling and efficiency Effluents on potato plant Spunta cultivar - سعود مهدكار; جميل عباس; علي كنجو (Latakia University Journal -Biological Sciences Series, 2023)
This research was carried out in the nursery of the Faculty of Agriculture (Tishreen University) with an area of 46.56 m2 allocated for agriculture. Potato tubers (Solanum tubrtosum L.) of the Spunta variety were planted in furrow 2.5 m long and 0.3 m wide. The distance between the furrow was 0.7 m and the distance between plants was 35 cm. The Surge irrigation method was used), and the experiment included the following treatments: The first treatment (control treatment): Surge irrigation on furrow with 100% of the water requirement, the second treatment: Surge irrigation on furrow with 95% of the water requirement, the third treatment: Surge irrigation on furrow with 90% of the water requirement. The fourth treatment: Surge irrigation on furrow with 85% of the water requirement. The fifth treatment: Surge irrigation on furrow with 80% of the water need. The sixth treatment: Surge irrigation on furrow with 75% of the water requirement. The results showed that the efficiencies are good (storage efficiency - homogeneity efficiency - addition efficiency - irrigation efficiency - water use efficiency), and therefore 75% irrigation efficiency is good, which is close to the values of sprinkler and drip irrigation. The results also showed that the water using efficiency of surge irrigation for the 80% treatment about 20 kg/m3/ha was better than the efficiency of the other treatments. In conclusion, we suggest adopting the method of surge irrigation on furrow to irrigate crops and vegetables grown on furrow to adopt it as a new method for modern irrigation.